Once Again! What Makes up Work Vitality? Refining the Construct and its Characteristics through a Qualitative Analysis - Nida Usman Jahangir; Sania Zahra Malik (Journal of Management and Research, 2020)
The concept of vitality, particularly work vitality, has been extensively explored in the existing literature, yet a comprehensive conceptualization and definition of this concept is not available. Based on the conservation of resource theory and the concept of salutogenesis, this exploratory study defined and studied the nature of the construct ‘work vitality’ as a psychological resource. Using a qualitative design, a comprehensive conceptual model of work vitality was developed. Thirty-three semi-structured interactive interviews were conducted. Based on social constructionism, thematic analysis was undertaken using the NVIVO software. The findings revealed that work vitality is a relatively constant, trait-like positive and energetic mindset characterized by the perceptions of aliveness, well-being and functioning at work. Five elements of work vitality, that is, perceptiveness, constancy, accessibility, restorability, and transferability were identified through qualitative empirical evidence. Hence, the current study contributes to the existing literature by explicating the nature of work vitality and identifying its elements. Finally, implications and future directions are discussed.